Genetic variation and phylogeographic structure of the cotton aphid, Aphis gossypii, based on mitochondrial DNA and microsatellite markers - Wang, Xing-Ya; Yang, Xian-Ming; Lu, Bin; Zhou, Li-Hong; Wu, Kong-Ming (Scientific reports, 2017)
Aphis gossypii , one of the most important agricultural pests in the world, can cause serious economic losses in the main crop-producing areas. To clarify issues such as the genetic differentiation, genetic structure, and demographic history of A. gossypii populations, we used 10 nuclear microsatellite loci (SSR) and two mitochondrial gene sequences ( COI and Cytb ) to investigate genetic diversity and population structure of A. gossypii populations that were collected from 33 sampling sites in China from different climatic zones. SSR and mtDNA data suggested low to moderate levels of genetic diversity. A star-shaped network of mtDNA haplotypes indicated that the maternal ancestor of China cotton aphids likely originated in Xinjiang. The POPTREE, STRUCTURE and principal coordinate analysis (PCoA) revealed two genetic clusters: an eastern and a western region group. Isolation by distance (IBD) results showed a positive correlation between geographic distance and genetic distance in the vast eastern region but not in the western region. Neutrality testing and mismatch distribution analysis provided strong evidence for a recent rapid expansion in most populations. Genetic bottleneck was not detected in A. gossypii populations of China. The present work can help us to develop strategies for managing this pest.